Analysis of early and treatment related deaths among children and adolescents with acute myeloid leukemia in Poland: 2005–2023 - Pawińska-Wąsikowska, Katarzyna; Czogała, Małgorzata; Bukowska-Strakova, Karolina; Surman, Marta; Rygielska, Monika; Książek, Teofila; Sadowska, Beata; Pac, Agnieszka; Skalska-Sadowska, Jolanta; Samborska, Magdalena; Wachowiak, Jacek; Ciebiera, Małgorzata; et al. (Frontiers in Pediatrics, 2024)
Background: A personalised approach to the treatment of acute myeloid leukemia (AML) in children and adolescents, as well as the development of supportive therapies, has significantly improved survival. Despite this, some patients still die before starting treatment or in an early phase of therapy before achieving remission. The study analysed the frequency, clinical features and risk factors for early deaths (ED) and treatment related deaths (TRD) of children and adolescents with AML. Methods: From January 2005 to November 2023, 646 children with AML treated in the centers of the Polish Pediatric Leukemia and Lymphoma Study Group according to three subsequent therapeutic protocols were evaluated: AML-BFM 2004 Interim (385 children), AML-BFM 2012 Registry (131 children) and AML-BFM 2019 (130 children). Results: Out of 646 children, early death occurred in 30 children, including 15 girls. The median age was 10.7 years (1 day -18 years). More than half of the patients (53%) were diagnosed with acute myelomonocytic leukemia (M5) and 13 % with acute promyelocytic leukemia (M3). The ED rate for the three consecutive AML-BFM protocols was 4.9% vs 5.3% vs 3.1%, respectively. In 19 patients, death occurred before the 15th day of treatment, in 11 between the 15th and 42nd day. The most common cause of death before the 15th day (ED15) was leukostasis and bleeding, whereas between the 15th and 42nd day (ED15-42), infections, mainly bacterial sepsis. A significant association was found between ED15 and high leukocyte count (> 10x10 9 /L), M3 leukemia (p< 0.001), and ED15-42 and age <1 year (p=0.029). In the univariate analysis only initial high leukocyte count >100x10 9 /L, was a significant predictor of early death. The overall TRD for the entire study period was 3.4%. The main cause of death were infections, mainly bacterial sepsis (10 children out of 22, 45.4%), Conclusions: Hyperleukocytosis remains significant factor of early mortality in patients with AML, despite the introduction of various cytoreductive methods. Infections are still the main cause of treatment related deaths. A more individualized approach by using new targeted drugs may be the therapeutic option of choice in the future.